A Proposal for Novel Standards of Histopathology Reporting for D3 Lymphadenectomy in Right Colon Cancer: The Mesocolic Sail and Superior Right Colic Vein Landmarks. Issue 4 (April 2020) - Garcia-Granero, Alvaro; Pellino, Gianluca; Giner, Francisco; Frasson, Matteo; Grifo Albalat, Isabel; Sánchez-Guillén, Luis; Valverde-Navarro, Alfonso A.; Garcia-Granero, Eduardo
Abstract : BACKGROUND: Strong agreement exists concerning the standards of pathologic reporting for total mesorectal excision and complete mesocolic excision. It represents a quality standard that correlates with survival. However, no agreed standards of reporting are available to define D3 lymphadenectomy for right colectomy. OBJECTIVE: The purpose of this study was to define anatomopathological standards of specimen quality obtained from the surgical specimen when an oncologic right hemicolectomy with D3 lymphadenectomy has been correctly performed. DESIGN: This study was conducted in 2 different phases. The first part consisted of a cadaver-based study of right colon anatomy, and the second part consisted of a prospective assessment of a series of surgical specimens obtained after right hemicolectomy for cancer. SETTINGS: The anatomic phase of the study was performed in collaboration with the University of Valencia Department of Anatomy and Embryology. The second part was performed at a colorectal unit of a tertiary hospital. PATIENTS: Seventeen cadavers were used for the first phase, and 65 surgical specimens were examined for the second part of the study. MAIN OUTCOME MEASURES: In each specimen, the pathologists looked for anatomic structures defined as markers of quality standards of the D3 lymphadenectomy during the first phase. Specimens were classified as complete, partial, and incomplete D3 lymphadenectomy. RESULTS: Twenty percent of specimens were classified as incomplete D3 lymphadenectomy, 31% as partial, and 49% as complete. A median number of 14 (6–64), 22 (11–47), and 29 (14–55) lymph nodes were isolated ( p = 0.01). Similarly, the median numbers of lymph nodes isolated in the area of D3 lymphadenectomy were 0 in incomplete, 1 (0–5) in Partial, and 3 (0–8) in Complete D3 lymphadenectomy specimens ( p = 0.0001). LIMITATIONS: A large multicenter study with adequate power is needed. CONCLUSIONS: We propose the right mesocolic sail and trunk of superior right colic vein as new and reproducible anatomopathologic standards of D3 lymphadenectomy in oncologic right hemicolectomy. See Video Abstract at http://links.lww.com/DCR/B149 . PROPUESTA PARA NUEVOS ESTÁNDARES HISTOPATOLÓGICOS EN LA LINFADENECTOMÍA D3 EN EL CÁNCER DE COLON DERECHO: LA VELA MESOCÓLICA Y LA VENA CÓLICA DERECHA SUPERIOR: ANTECEDENTES: Existe un claro acuerdo sobre los estándares de calidad patológicos para la escisión total del mesorrecto y la escisión completa del mesocolon. Son considerados "estándar de calidad" que se correlaciona con la supervivencia. Sin embargo, no se dispone de estándares de calidad para definir la linfadenectomía D3, en la colectomía derecha. OBJETIVO: Definir los estándares anatomopatológicos de calidad obtenidos de una muestra quirúrgica, cuando se ha realizado correctamente una hemicolectomía derecha oncológica, con linfadenectomía D3. DISEÑO: Dos fases diferentes. La primera parte consistió en un estudio basado en la anatomía del colon derecho, realizado en cadáveres, y la segunda parte consistió en una evaluación prospectiva de una serie de muestras quirúrgicas obtenidas después de la hemicolectomía derecha para cáncer. AJUSTES: La fase anatómica del estudio se realizó en colaboración con el Departamento de Anatomía y Embriología de la Universidad de Valencia. La segunda parte se realizó en la Unidad Colorrectal de un hospital terciario. PACIENTES: Se utilizaron diecisiete cadáveres para la primera fase y se examinaron 65 muestras quirúrgicas para la segunda parte del estudio. PRINCIPALES MEDIDAS DE RESULTADO: En cada muestra, los patólogos buscaron estructuras anatómicas definidas, como marcadores de los estándares de calidad de la linfadenectomía D3, durante la primera fase. Las muestras se clasificaron como linfadenectomía D3 completa, parcial e incompleta. RESULTADOS: El veinte por ciento de las muestras se clasificaron como "Linfadenectomía D3 Incompleta", el 31% como "Parcial" y el 49% como "Completa." Se aisló una media de 14 (6-64), 22 (11-47) y 29 (14-55) ganglios linfáticos respectivamente (p = 0, 01). Del mismo modo, el número medio de ganglios linfáticos aislados en el área de la linfadenectomía D3 fue 0 en "Incompleta", 1 (0-5) en "Parcial" y 3 (0-8) en muestras de "Linfadenectomía D3 Completa" (p = 0, 0001). LIMITACIONES: Se necesita un estudio multicéntrico con potencia adecuada. CONCLUSIONES: Proponemos la vela mesocólica derecha y el tronco de la vena cólica derecha superior, como estándares anatomopatológicos nuevos y reproducibles de linfadenectomía D3, en hemicolectomía derecha oncológica. Consulte Video Resumen en http://links.lww.com/DCR/B149 .